The EFFECT OF KNOWLEDGE LEVEL OF TYPE II DIABETES MELLITUS PATIENTS ON OUTPATIENT COMPLIANCE WITH OAD THERAPY AT COMMUNITY HEALTH CENTERS OF GIANYAR DISTRICT DURING THE COVID-19 PANDEMIC - Tresnayanthi, Kadek Ayu Sri; Mahendra, Agung Nova; Indrayani, Agung Wiwiek; Sumardika, I Wayan (E-Jurnal Medika Udayana; Vol 12 No 7 (2023): E-Jurnal Medika UdayanaDO - 10.24843/MU.2023.V12.i07.P07, 2023)
Type II Diabetes Mellitus dominates DM cases in primary health care. The limitat ions type II DM services during the COVID-19 pandemic by Puskesmas risk decreasing the level of knowledge and adheren ce to OAD therapy i n type II patients. A good level of patient knowledge abo ut type II DM can influence a p atient’s decision to comply with OAD therapy during the COVID-19 pandemic . This study aims describe effect of knowledge level type II Diabetes Mellit us patients on OAD therapy adherence at Gianyar district health center durin g the COVID-19 pandemic. The m ethod used analytic method with a cross-sectional approach during the period March-August 2022 in four health centers of Gianyar regency. The level of measurement using the Diabetes Knowledge Questionnaire (DKQ-24) and therape utic compliance with the Moris ky Medication Adherence Scales (M MAS-8) questionnaire, the data was taken using google form. Based level knowledge 96 respondents (43,7%) high knowled ge, 46 people (48%) moderate knowledge, and 8 people (8,3%) low knowledge. M eanwhile based on level of compliance, there were 53 people (55 ,2%) with hight compliance, 35 people (36,5%) with moderate compliance, and 8 people (8,3%) with low compliance. The level knowledge and compliance to patients during COVID-19 was moderate know ledge and high co mpliance, may be influenced by the ease of acc ess to information for patients in internet . Outpatient type II DM at the Gianyar district health center during the C OVID-19 pandemic mo derate knowledge and high compliance, and there was a sig nificant effect b etween the level of knowledge to therapy adher ence and a p-value of 0,000. Keywords : knowledge, c ompliance , influence , diabetes mellitus type II , pandemic COVID- 19.